2020
DOI: 10.3233/jpd-191787
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of α-Synuclein Protein Levels by an Intracellular Single-Chain Antibody

Abstract: Background: Accumulation of ␣-synuclein (␣Syn) in the dopaminergic neurons is a common pathology seen in patients with Parkinson's disease (PD). Overproduction of ␣Syn potentiates the formation of oligomeric ␣Syn aggregates and enhances dopaminergic neuron degeneration. Downregulating intracellular monomeric ␣Syn prevents the formation of ␣Syn oligomers and is a potential therapeutic strategy to attenuate the progression of PD. Objective: The purpose of this study is to investigate the efficacy of gene deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We previously demonstrated that transduction of NAC32, a single-chain antibody against the NAC of αSyn, downregulated αSyn protein in SH-SY5Y cells and adult Sprague Dawley rats nonselectively overexpressing αSyn in the nigra [ 9 ]. In this study, we characterized the behavior, and histological response of AAV-NAC32 in the animals selectively expressed αSyn in nigra DA neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that transduction of NAC32, a single-chain antibody against the NAC of αSyn, downregulated αSyn protein in SH-SY5Y cells and adult Sprague Dawley rats nonselectively overexpressing αSyn in the nigra [ 9 ]. In this study, we characterized the behavior, and histological response of AAV-NAC32 in the animals selectively expressed αSyn in nigra DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence (813 bp) encoding a single-chain intrabody (NAC32; tagged with FLAG and 6× Histidine at N-and C-terminals, respectively) against the nonamyloid component region of human αSyn was made by chemical synthesis (Genomics Ltd., New Taipei City, Taiwan) and then cloned into an AAV shuttle plasmid pAAV-MCS (Agilent Technologies, Santa Clara, CA, USA) at EcoRI and BamHI restriction enzyme sites. The DNA sequence (589 bp) of a post-transcriptional regulatory element derived from the woodchuck hepatitis B virus (WPRE; GeneBank accession # J04514) was synthesized and introduced into the 3’-end of NAC32 at BamHI and BglII sites, generating the vector plasmid pAAV-NAC32 [ 9 ]. The coding DNA sequence (711 bp) of the red fluorescence protein mCherry was synthesized and used to replace the NAC32 coding sequence on pAAV-NAC32 by cloning at EcoRI and BamHI sites resulting in the vector plasmid pAAV-mCherry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a scFv intrabody, NAC32, binding to the NAC fragment of α-syn, was isolated from a yeast-displayed nonimmune human scFv library by sequential magnetic bead enrichment and flow cytometric sorting and shown to inhibit α-syn-induced cytotoxicity in vitro [ 62 ]. Subsequently, Chen and collaborators demonstrated that recombinant AAV5 expressing NAC32 scFv increases the survival of dopaminergic neurons and improves locomotor behavior after intracranial administration to rats overexpressing α-syn [ 63 , 64 ].…”
Section: Recombinant Antibody Fragmentsmentioning
confidence: 99%
“…Two scFv nanobodies (NAC32 and VH14) that recognize aa53–87 of the α -syn non-amyloid component (NAC) region were developed, and the coding sequences incorporated into adeno-associated virus (AAV) constructs to be used as intracellularly expressed nanobodies, termed intrabodies [ 186 ]. Co-transfection of each construct with AAV- α syn constructs into HEK293 and SH-SY5Y cells demonstrated that co-expression of α -syn and NAC32, but not VH14 intrabodies, downregulated α -syn protein, but not α -syn mRNA [ 187 ]. Co-administration of AAV-NAC32 with AAV- α syn to rats, reduced α -syn expression in the substantia nigra and striatum, and spared dopaminergic termini in the striatum.…”
Section: Nanobodies As Dmtmentioning
confidence: 99%